If it's not what You are looking for type in the equation solver your own equation and let us solve it.
57-3=2y+9
We move all terms to the left:
57-3-(2y+9)=0
We add all the numbers together, and all the variables
-(2y+9)+54=0
We get rid of parentheses
-2y-9+54=0
We add all the numbers together, and all the variables
-2y+45=0
We move all terms containing y to the left, all other terms to the right
-2y=-45
y=-45/-2
y=22+1/2
| 8a+4=6a+4 | | 3(2-k)=-3k=2 | | x/4-19=20 | | -3(6+3x)=-(6x+3) | | 6+8x=11x | | y/5+10=11 | | -3x+10=-38 | | 6(m-4)+5=-5(6-m) | | -2x+8(x+7)=7+5(1-x) | | -8-(6-8m)=2(m-1) | | 51=5(3a+6)-8 | | 7(4-4x)=-8(1+3x) | | 30.25x=60 | | 17=3-2(2f-1) | | 5x+3–3x+2=35 | | -(7x-1)+14=21 | | 8+w/2=11 | | 0.05x=37.25 | | 2m=78 | | 13-3k=7 | | 26+4.25.x=60 | | -3(-6b-4)=6(4b+6) | | -6u-36=−42 | | -4(m-1)=-8 | | -6u-36= | | 16/4=v | | 9.43=k−9.64 | | 2(4x+2)+x=9x-4 | | 30+x=3/5 | | 19t-16t=48 | | 3/4(8x−12)=4x−4 | | 72=27+9s |